Comparison of teprenone and famotidine against gastroduodenal mucosal damage in patients taking low‐dose aspirin. (December 2014) - Takeuchi, Toshihisa; Ota, Kazuhiro; Harada, Satoshi; Kojima, Yuichi; Inoue, Takuya; Iwakiri, Ryuichi; Sakata, Yasuhisa; Fujimoto, Kazuma; Fujita, Tsuyoshi; Azuma, Takeshi; Higuchi, Kazuhide
Abstract: Background and Aim: Proton‐pump inhibitors are known to be effective in the treatment and prevention of ulcers related to low‐dose aspirin (LDA), but few reports address H2 ‐receptor antagonists (H2RAs) and gastroprotective agents (GPs). This study was intended to compare the therapeutic effects of an H2RA and a GP against gastroduodenal mucosal injuries in patients taking LDA. Methods: The subjects consisted of patients requiring continuous LDA treatment, in whom no peptic ulcer was found on endoscopy at enrollment. The patients were randomized to either famotidine 20 mg/day (group F) or teprenone 150 mg/day (group T). The study medication was administered for 12 weeks. The patients underwent endoscopy after administration of the study medication in order to obtain a Lanza score. Results: A total of 66 patients (38 in group F, 28 in group T) were included in the efficacy analysis population. The Lanza score changed as follows: in group F, it improved significantly, from 0.89 ± 1.03 (mean ± standard deviation) before medication to 0.39 ± 0.75 after medication ( P = 0.006); in group T, no significant difference was observed: 0.75 ± 0.93 before medication and 0.68 ± 0.82 after medication. Conclusion: Famotidine is better than teprenone in terms of reducing the number of the erosions under use of LDA.